Polystyrene nanoplastics exposure causes erectile dysfunction in rats - Ming Wang; Bangshun Dai; Qiushi Liu; Xiaobin Wang; Yunzheng Xiao; Guilong Zhang; Hui Jiang; Xiansheng Zhang; Li Zhang (Ecotoxicology and Environmental Safety, 2024)
Polystyrene nanoplastics (PS-NPs), emerging and increasingly pervasive environmental contaminants, have the potential to cause persistent harm to organisms. Although previous reports have documented local accumulation and adverse effects in a variety of major organs after PS-NPs exposure, the impact of PS-NPs exposure on erectile function remains unexplored. Herein, we established a rat model of oral exposure to 100 nm PS-NPs for 28 days. To determine the best dose range of PS-NPs, we designed both low-dose and high-dose PS-NPs groups, which correspond to the minimum and maximum human intake doses, respectively. The findings indicated that PS-NPs could accumulate within the corpus cavernosum and high dose but not low dose of PS-NPs triggered erectile dysfunction. Moreover, the toxicological effects of PS-NPs on erectile function include fibrosis in the corpus cavernous, endothelial dysfunction, reduction in testosterone levels, elevated oxidative stress and apoptosis. Overall, this study revealed that PS-NPs exposure can cause erectile dysfunction via multiple ways, which provided new insights into the toxicity of PS-NPs.